(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
This study aims to look at the fingerprints in the crime of murder at the Makassar Police and monitor the criminal acts involved in the fingerprint examination process at the level of murder at the Makassar Police. This study uses a juridical empirical research method which is taken from data using primary data with interviews and secondary data by processing data from primary legal materials, secondary law and tertiary law. Based on the results of the research, it is known that fingerprint evidence as an indication in an investigation of a murder crime is clear and has the same validity in front of a court as other evidence. The strict completeness contained in the investigation process, namely the change in authenticity at the scene of the case, the absence of complete facilities and infrastructure, is the investigator experience in carrying out investigations, and legal factors. There is a need for a special law that regulates fingerprint evidence and there is a need for cooperation between the police and the public in criminal acts that occur, at the scene of the case. Abstrak Penelitian ini bertujuan untuk mengetahui kedudukan sidik jari dalam penyidikan tindak pidana pembunuhan di Polrestabes Makassar dan mengetahui kendala-kendala yang terdapat dalam proses pelaksanaan pemeriksaan sidik jari tingkat penyidikan tindak pidana pembunuhan di Polrestabes Makassar. Penelitian ini menggunakan metode penelitian bersifat yuridis empiris diambil dari data menggunakan data primer dengan melakukan wawancara dan data sekunder dengan mengolah data dari bahan hukum primer, hukum sekunder dan hukum tersier. Berdasarkan hasil penelitian diketahui kedudukan alat bukti sidik jari sebagai petunjuk dalam penyidikan tindak pidana pembunuhan sudah jelas sah dan sama keabsahannya di depan pengadilan dengan alat bukti yang lain. Adapun kendala-kendala yang terdapat dalam proses penyidikan yaitu perubahan keaslian di tempat kejadian perkara, ketiadaan kelengkapan sarana dan prasarana, kurangnya pengalaman penyidik dalam melakukan penyidikan, dan faktor hukum. Perlu dibuat Undang-Undang khusus yang mengatur langsung tentang alat bukti sidik jari dan perlu adanya kerja sama antara pihak Kepolisian dan masyarakat dalam menanggapi tindak pidana yang terjadi khususnya di tempat kejadian perkara.